2011
DOI: 10.1080/03637751.2010.542579
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Consumption of Political TV Satire: Affinity for Political Humor,The Daily Show, andThe Colbert Report

Abstract: Content analyses have focused on the messages offered in political TV satire, and the communication discipline is amassing solid empirical evidence concerning a range of effects derived from this style of programming. However, there is remarkably little understanding of who is tuning in to view political TV satire beyond the audience being dominated by a younger demographic. It is imperative to have a better understanding of the audience for these programs in order to place any effects in their proper context.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 39 publications
1
51
1
1
Order By: Relevance
“…Recent efforts have suggested that it is not a matter of simply considering key demographic variables and prior patterns of media consumption but rather an individual's desire to seek out and appreciate humorous political content (Hmielowski et al, 2011). Various measures have been applied to the study of nontraditional media content including news content affinity, the need for humor (NFH), and the newly created affinity for political humor scale (AFPH; Coe et al, 2008;Hmielowski et al, 2011;Holbert et al, 2013;Matthes, 2013).…”
Section: Affinity For Political Humor Anxiety Reduction Humor Orienmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent efforts have suggested that it is not a matter of simply considering key demographic variables and prior patterns of media consumption but rather an individual's desire to seek out and appreciate humorous political content (Hmielowski et al, 2011). Various measures have been applied to the study of nontraditional media content including news content affinity, the need for humor (NFH), and the newly created affinity for political humor scale (AFPH; Coe et al, 2008;Hmielowski et al, 2011;Holbert et al, 2013;Matthes, 2013).…”
Section: Affinity For Political Humor Anxiety Reduction Humor Orienmentioning
confidence: 99%
“…The AFPH scale was designed to tap four dimensions of an individual's affinity for political humor, including (a) the desire to make sense of incongruent information, (b) an interest in promoting a sense of superiority, (c) the reliance on humor as a way to reduce anxiety or stress, and (d) the value of humor for social cohesion (Hmielowski et al, 2011). Preliminary research has treated the AFPH scale as a combined single measure, one that has emerged as an important and effective predictor of political satire consumption (Hmielowski et al, 2011).…”
Section: Affinity For Political Humor Anxiety Reduction Humor Orienmentioning
confidence: 99%
See 1 more Smart Citation
“…The Affinity for Political Humor measure is an 11-item index (see Hmielowski et al, 2011). Personal agreement for each of the 11 items was assessed using 5-point scales ranging from 1 (strongly disagree) to 5 (strongly agree), with the higher end of the scale indicating a greater affinity for political humor.…”
Section: Methodsmentioning
confidence: 99%
“…Citizens who are older tend to consume these media outlets with greater frequency. In addition, the only consistent predictor of various forms of entertainment-oriented political media (e.g., The Daily Show with Jon Stewart, The Colbert Report) is age, but it is those who are younger who are turning to this content more often (e.g., Hmielowski, Holbert, & Lee, 2011;Young & Tisinger, 2006). Methodologically, the field of political communication, as well as every other field that employs the use of survey methodology to address various research questions and hypotheses, is becoming all the more aware of the inherent weaknesses of using traditional landlines as the only telecommunications mode by which to generate representative samples of a population (Link, Battaglia, Frankel, Osborn, & Mokdad, 2007).…”
mentioning
confidence: 98%